Behavior of soil aggregates in reclaimed farmland with different restoration durations: Mediating factors and mechanisms - Zhaoxinyu Liu; Junying Li; Lina Gao; Xinju Li; Wen Song; Luofan Li; Yulong Zang; Gengdi Zhang (Geoderma)
The recovery of soil aggregates is crucial for improving soil quality in highly compacted reclaimed farmlands in coal mining subsidence areas. This study aimed to explore the key factors and mechanisms affecting aggregate recovery in reclaimed mine soil (RMS). Surface soil samples (0 ∼ 20 cm) were collected from reclaimed farmlands with varying reclamation durations (0, 2, 6, 12, 16, and 22 years) and adjacent non-subsidence cultivated soil (NCS). A total of 20 soil indicators were analyzed. Complex network theory was then applied to explore their interrelationships and identify critical factors influencing aggregate distribution. The results showed that mechanical compaction during geomorphic reshaping disrupted macroaggregates, reduced aggregate stability, accelerated organic carbon mineralization, and diminished microbial activity. This also resulted in increased complexity and disorder of soil property interactions. After 22 years of reclamation, the proportion of 2 ∼ 0.25 mm aggregates increased by 25.92 %, while 0.25 ∼ 0.053 mm aggregates decreased by 40.93 %. The mean weight diameter and geometric mean diameter increased by 34.48 % and 69.54 %, respectively. Soil organic carbon (SOC) increased by 250.94 %, and microbial biomass by 123.07 %. However, RMS still exhibited differences in aggregate distribution, stability, SOC accumulation, and system functionality compared with the NCS. Soil aggregates, particularly macroaggregates, served as mediators within the RMS system. In the early stages of reclamation, inorganic cementing agents were crucial for maintaining RMS aggregation and SOC sequestration. Over time, particulate organic carbon and microbial activity became dominant in aggregate formation. Iron-aluminum oxides, particularly amorphous forms, facilitated macroaggregate formation and SOC stabilization.